Effect of pruning time, hydrogenated cyanamide and irrigation upon anticipated production of green figs - Norberto, Paulo Márcio; Chalfun, Nilton Nagib Jorge; Pasqual, Moacir; Veiga, Ruben Delly; Mota, José Hortêncio (Pesquisa Agropecuaria Brasileira, 2001)
The objective of this work was to evaluate the effect of the pruning time, the application of hydrogenated cyanamide (Dormex), and of the irrigation on plant development and on the premature production of green figs (Ficus carica L.), cultivar Roxo de Valinhos, for the industry. Treatments consisted of ten pruning times, with intervals of 15 days, application of the solution at 2% of hydrogenated cyanamide, application of hydrogenated cyanamide + irrigation, and irrigation three times a week, supplying 40 L of water/plant/day. The pruned plants at the May’s second fortnight, which were irrigated and received hydrogenated cyanamide, presented a larger number of fruits as average, larger branch length, and produced off-season fruits (October); into more precocious prunings (from April’s first fortnight to May’s first fortnight) there was a prolongation in the plant cycle, although the April’s first fortnight had facilitated the off-season fig crops; in the later pruning times (from June’s first fortnight to August’s second fortnight) the treatments referred to hydrogenated cyanamide + irrigation, and irrigation, presented a larger length of branch and larger number of fruits, but the crops were initiated at the normal period of the crop.